Morning spot urinary cortisol-to-creatinine ratio: a novel screening tool for assessing excess cortisol secretion - Liu, Yingning; Zhang, Ping; Zhang, Simin; Gao, Ying; Mu, Yiqing; Lian, Hong; Ren, Qian; Cai, Xiaoling; Zhou, Xianghai; Han, Xueyao; Ji, Linong; Zou, Xiantong (Frontiers in Endocrinology, 2025)
ContextCurrent screening methods for hypercortisolism face limitations in clinical practice.ObjectiveOur study proposes and validates a novel biomarker, the morning spot urinary cortisol-to-creatinine ratio (UCCR), as a simpler alternative for assessing excess cortisol secretion.MethodsThis cross-sectional study was conducted in Chinese hospitalized patients, comprising a cohort of 167 patients who underwent the 1mg overnight dexamethasone suppression test (1mg DST). Urinary free cortisol level (UFC) and creatinine were measured using morning spot urine, and UCCR was subsequently calculated. Receiver operating characteristic (ROC) curve analysis was used to assess the performance of these parameters in predicting the results of the 1mg DST.ResultsMorning spot UCCR showed significant correlations with 24-hour UFC and was independently associated with a positive 1mg DST result. The ROC AUCs for morning spot UCCR were 0.642 (0.549-0.734) and 0.762 (0.665-0.859) in predicting cortisol >1.8 µg/dL and >5.0 µg/dL post-1mg DST, respectively, comparable to those of 24-hour UFC and UCCR. Morning spot UCCR demonstrated high sensitivity of 71.4% and 86.4% for predicting post-DST cortisol >1.8 µg/dL and 5.0 µg/dL, respectively. The negative predictive value (NPV) of morning spot UCCR was 83.5% for cortisol >1.8 µg/dL and 96.8% for >5.0 µg/dL post-1mg DST. A significant reduction in ROC AUC was observed in males, with a borderline decrease noted in patients with diabetes.ConclusionsMorning spot UCCR is a reliable alternative for the initial evaluation of cortisol secretion and is particularly useful for excluding cortisol excess. Nonetheless, caution is advised when applying this test in males or patients with diabetes.